Expanding Opportunities: A Framework for Gender and Socially-Inclusive Climate Resilient Agriculture - Huyer, Sophia; Simelton, Elisabeth; Chanana, Nitya; Mulema, Annet Abenakyo; Marty, Edwige (Frontiers in Climate, 2021)
Limiting global warming to the 2°C target that countries have committed to in the 2015 Paris Agreement, and reaching the Sustainable Development Goals by 2030, will require large-scale expansion of climate-resilient approaches in agriculture and food systems. In order to achieve the scale of change required, coordinated action is needed from global to local levels, from research to policy and investment, and across private, public and civil society sectors. But at the same time, differential approaches are needed to address gender equality and women’s concerns in climate-resilient agriculture. For improved adoption, more attention needs to be given to the institutions that may constrain change and innovation in the poorest and most vulnerable groups. The importance of participatory approaches as well as embedding equality, more equal power relations and social justice into both the policy and practice of CSA is necessary. Given inequality constraints, how can the scaling-up of climate-resilient agriculture approaches be consistent with gender equality, and integrate the conditions and mechanisms necessary to address inequality? This article sets out a conceptual framework for scaling up climate resilient agriculture approaches that are gender and socially-inclusive. The idea is to identify potential pathways for developing a gender- and socially-inclusive set of options and strategies, in four key dimensions: climate resilient technologies and practices; climate information services that reach under-reached groups; inclusive finance mechanisms; and promoting leadership in decision-making.